Evaluation of VIDAS®Listeria monocytogenes Xpress (LMX) for the Detection of Listeria monocytogenes in a Variety of Foods: First Action 2013.11. (27th November 2019) - Crowley, Erin; Bird, Patrick; Flannery, Jonathan; Benzinger, Jr, M Joseph; Fisher, Kiel; Boyle, Megan; Huffman, Travis; Bastin, Ben; Bedinghaus, Paige; Judd, Will; Hoang, Thao; Agin, James; et al.
Abstract: The VIDAS ® Listeria monocytogenes Xpress (LMX) is an automated rapid screening enzyme immunoassay for the detection of Listeria monocytogenes in food products. The VIDAS LMX method was compared in a multi-laboratory collaborative study to AOAC Official Method 993.12 Listeria monocytogenes inMilk and Dairy Products reference method following current AOAC guidelines. A total of 14 laboratories participated, representing government and industry, throughout the United States. One matrix, queso fresco (soft Mexican cheese), was analyzed using two different test portion sizes, 25 and 125 g. Samples representing each portion size were artificially contaminated with L. monocytogenes at three levels: an uninoculated control level [0 colony forming units (CFU)/test portion], a low inoculum level (0.2–2 CFU/test portion), and a high inoculum level (2–5 CFU/test portion). For this evaluation, 1800 unpaired replicate test portions were analyzed by either the VIDAS LMX or AOAC 993.12. Each level was analyzed using the Probability of Detection (POD) statistical model. For the low-level inoculated test portions, difference in collaborator POD (dLPOD) values of 0.04, (–0.08, 0.15) and 0.01, (–0.10, 0.13), with 95% confidence intervals, were obtained, respectively, for 25 and 125 g test portions. The range of the confidence intervals for dLPOD values for both the 25 and 125 g test portions contain the point 0.0 indicating no statistically significant difference in the number of positive samples detected between the VIDAS LMX and the AOAC method. In addition to Oxford Agar (OXA), VIDAS LMX test portions were confirmed using Agar Listeria Ottavani and Agosti (ALOA), a proprietary chromogenic agar for the identification and differentiation of L. monocytogenes and Listeria species. No differences were observed between the two selective agars. The VIDAS LMX method, with the optional ALOA agar confirmation method, was adopted as Official First Action status for the detection of L. monocytogenes in a variety of foods.